Environmental Sampling for Severe Acute Respiratory Syndrome Coronavirus 2 During a COVID-19 Outbreak on the Diamond Princess Cruise Ship. (21st July 2020) - Yamagishi, Takuya; Ohnishi, Makoto; Matsunaga, Nobuaki; Kakimoto, Kensaku; Kamiya, Hajime; Okamoto, Kiyoko; Suzuki, Motoi; Gu, Yoshiaki; Sakaguchi, Mikiyo; Tajima, Taichi; Takaya, Saho; Ohmagari, Norio; et al.
Abstract: During a COVID-19 outbreak on the Diamond Princess cruise ship we sampled environmental surfaces after passengers and crew vacated cabins. SARS-CoV-2 RNA was detected in 58 of 601 samples (10%) from case cabins 1–17 days after cabins were vacated but not from noncase cabins. There was no difference in detection proportion between cabins of symptomatic (15%, 28/189; cycle quantification [Cq], 29.79–38.86) and asymptomatic cases (21%, 28/131; Cq, 26.21–38.99). No SARS-CoV-2 virus was isolated from any of the samples. Transmission risk of SARS-CoV-2 from symptomatic and asymptomatic patients may be similar and surfaces could be involved in transmission.